Analisis Fluktuasi Harga Daging Ayam Broiler di Provinsi Jawa Timur Periode 2019-2023 - Harsita, Pradiptya Ayu; Jadmiko, Mochammad Wildan; Amam, Amam; Kartanegara, Antoni Ahmad Yusuf (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Broiler chicken is one of the strategic livestock commodities in Indonesia, because in addition to being easily obtained by the public, the price of broiler chicken meat is relatively affordable. This study aims to analyze the fluctuation of broiler chicken meat prices and analyze the factors that influence the fluctuation of broiler chicken meat prices in East Java Province. The analysis in this study uses the ARCH / GARCH method to analyze the level of fluctuation and uses the VAR / VECM model to analyze the factors that influence the fluctuation of chicken meat prices in East Java Province. The research variables include the price of broiler chicken meat in East Java Province, the price of rice (as a complementary good), the price of eggs (as a substitute good), the world meat price index, inflation, the rupiah exchange rate, and interest rates. The results of the study indicate that the fluctuation of broiler chicken meat prices in East Java Province in the 2019-2023 period is included in the low category. The results of the short-term estimation show that there are no variables that have a significant effect on the fluctuation of broiler chicken meat prices, while the results of the long-term estimation show that the variables that have a significant effect on changes in broiler chicken meat prices in East Java Province are the price of rice, the price of eggs, the world meat price index, inflation, the rupiah exchange rate, and interest rates.